OPTIMIZING TRANSPORTATION COST FOR BIOMASS SUPPLY CHAIN - Kousar, Sajida; Sangi, Maryam Nazir; Kausar, Nasreen; Agarwal, Praveen; Ozbilge, Ebru; Bulut, Alper (VINCA INST NUCLEAR SCI, 2023)
Biomass conversion is largely impacted by the cost of transporting biomass mate-rials. As a result, businesses need optimization solutions to optimize their transport operations, allocate resources effectively, and reduce their environmental impact. As part of the process of biomass conversion, this paper discusses the transport and biomass optimization problem in detail. The paper presents optimization of transportation cost of two biomass products, natural gas, and bio fuel during the process of biomass conversion final products depending on the transport routes and other factors.
Keywords: biomass; biomass supply chain; optimization; transportation; FOREST BIOMASS; DESIGN; BIOFUEL; MODEL; Thermodynamics